2010
DOI: 10.1590/s0100-40422010000200015
|View full text |Cite
|
Sign up to set email alerts
|

Modification of a Brazilian smectite clay with different quaternary ammonium salts

Abstract: In this work, a smectite clay from the State of Paraiba, Brazil, was treated with six different types of ammonium salts, which is an usual method to enhance the affinity between the clay and polymer for the preparation of nanocomposites. The clays, before and after modification, were characterized by X ray diffraction. The conformation of the salts within the platelets of the clay depended on the number of long alkyl chains of the salt. The thermal stability of the clays was also studied. The ammonium salts th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 27 publications
5
19
0
6
Order By: Relevance
“…The temperature and intensity of the first two peaks related to the dehydration process decreased with the increasing amount of the added surfactant. In addition, the organo-montmorillonites are subjected to a thermal effect at the temperature interval 270-450 °C corresponding to the alkylammonium decomposition [44]. As expected, the mass loss in the whole temperature interval 25-1200 °C increased with increasing amount of the alkylammonium cations.…”
Section: Characterization Of Prepared Organo-montmorillonitessupporting
confidence: 58%
“…The temperature and intensity of the first two peaks related to the dehydration process decreased with the increasing amount of the added surfactant. In addition, the organo-montmorillonites are subjected to a thermal effect at the temperature interval 270-450 °C corresponding to the alkylammonium decomposition [44]. As expected, the mass loss in the whole temperature interval 25-1200 °C increased with increasing amount of the alkylammonium cations.…”
Section: Characterization Of Prepared Organo-montmorillonitessupporting
confidence: 58%
“…This localization is a function of the nature of the nanoparticles, and thus depends on the size, shape, and chemical surface of the nanoparticles. That is why most often, nanoparticles are organomodified either by chemical grafting [15][16][17] or by ionic exchange [18][19][20][21] in order to be more compatible with blend components. However, while some studies have shown that adding organoparticles could be similar to adding block copolymers, when the latter are located at the interface, no additional relaxation phenomenon has as yet been observed.…”
Section: Introductionmentioning
confidence: 99%
“…The swelling can help the intercalation and exfoliation process of the clay layers in the polymer matrix, thus forming polymer nanocomposites. It is known that each clay nanostructure presents different properties; generally the intercalation structure may improve the impact property and exfoliation structure may improve the water barrier and gas barrier property and also anti-flammability characteristics 12,11 . Various characterization techniques are used to evaluate the characteristics of these new materials.…”
Section: Introductionmentioning
confidence: 99%